2015
DOI: 10.1074/mcp.m114.046763
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Analysis of Interaction between a Plant Virus and Its Vector Insect Reveals New Functions of Hemipteran Cuticular Protein

Abstract: Numerous viruses can be transmitted by their corresponding vector insects; however, the molecular mechanisms enabling virus transmission by vector insects have been poorly understood, especially the identity of vector components interacting with the virus. Here, we used the yeast two-hybrid system to study proteomic interactions of a plant virus (Rice stripe virus, RSV, genus Tenuivirus) with its vector insect, small brown planthopper (Laodelphax striatellus). Sixty-six proteins of L. striatellus that interact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
95
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 101 publications
(98 citation statements)
references
References 61 publications
0
95
0
Order By: Relevance
“…Future work includes comparison of transmission capacity between two cryptic species (MED and MEAM1) of B. tabaci and molecular mechanisms. In the previous experiment we found that MED is more effective in transmission of CCYV than MEAM1 (unpublished data), and studies of protein-protein interactions between virus and vector may reveal the mechanisms of difference in transmission ability929.…”
Section: Discussionmentioning
confidence: 75%
“…Future work includes comparison of transmission capacity between two cryptic species (MED and MEAM1) of B. tabaci and molecular mechanisms. In the previous experiment we found that MED is more effective in transmission of CCYV than MEAM1 (unpublished data), and studies of protein-protein interactions between virus and vector may reveal the mechanisms of difference in transmission ability929.…”
Section: Discussionmentioning
confidence: 75%
“…qRT-PCR was performed using the Roche LightCycler ® 480II. The thermal cycling program was as follows5758: 95 °C for 15 min, 40 cycles at 95 °C for 15 s and at 60 °C for 30 s. The gene expression of rice UBQ5 was used as an internal control.…”
Section: Methodsmentioning
confidence: 99%
“…Identification of putative components could lead to new strategies to interdict viral spread. During the past decades, a number of virus and insect proteins involved in this transmission process have been identified in some virus-vector combinations (11)(12)(13). However, mechanisms underlying transovarial transmission of viruses have rarely been reported, especially for circulative-nonpropagative viruses, because this group of viruses is generally believed not able to replicate and transovarially transmit in their insect vectors.…”
mentioning
confidence: 99%